Poczucie podmiotowości i zaangażowanie pracowników we współczesnych samozarządzających się organizacjach = Sense of subjectivity and employee engagement in contemporary self-managing organizations - Zygadło, Andrzej (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In this article, the author presents various conditions (both on a global and local scale) of creating an organizational culture in companies operating on the contemporary labor market. The author draws attention to the factors necessary for the emergence of a high level of employee engagement and their sense of subjectivity in their Professional work.
Keywords: kultura pracy; kultura organizacyjna; zaangażowanie pracownika; poczucie podmiotowości; organizacje turkusowe; work culture; organizational culture; employee engagement; sense of subjectivity; teal organizations